Analysis of kinematic and compliance of passive suspension system using Adams car - Ikhsan, N.; Ramli, R.; Alias, A. (2014)
Experimental approach is usually use as the way to develop or modify suspension system to obtain maximum ride comfort and handling characteristic. This approach is a time consuming process, costly, and may not guarantee the optimum solution. In this paper, a half-car body of actual suspension system based on PROTON WRM 44 P0-34 was model using multi-dynamic software, MSC/ADAMS-Car. There were total of 10 components for each front McPherson strut and rear Multilink suspensions that consist of different joint types and degree of freedom. The model were develop by defining the location of hard-point or coordinate before specific all the component characteristic and joint type. The complete suspension model is simulated using vertical-parallel and vertical-oppose movement test on MSC/ADAMS Car, same with the actual experimental parameter setup. The kinematic and compliance (K&C) of simulation is compared with the experimental data to verify the suspension model. It is expected that simulated and experimental produce the identical data pattern with very minimal percentage error. Further investigation can be done to improve or optimize the performance of the suspension system once the model is verified.